The geography of patents: The spatial distribution of inventiveness in Germany - Greif, Siegfried (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
The patents system provides a suitable instrument for monitoring and analysing developments both of a technological/scientific and of an economic nature. It also lends itself for application in connection with the analysis of the spatial distribution of inventiveness. The common aim of the studies reported on in this article is to gain a greater understanding of the spatial structure of patenting activity, of the R&D activities associated with this, and of the innovative potential which it lays bear. An even greater insight can be gleaned if the patent data is considered in a more discriminatory fashion, distinguishing for example between spatial units, patent-claimant registration categories, technical categories and periods of observation, and if this data is linked to further data on such matters as population, type of employment, and research and development activity. The findings of these studies reveal the spatial distribution and the substantive structure of inventiveness — and the fruits it bears — to be quite specific in character and to be patterned by a variety of determining factors.
Keywords: Article